STRESS ANALYSIS OF SUBMARINE PIPELINE AT IN- PLACE, HYDROTEST AND OPERATION CONDITION (CASE STUDY: SUBMARINE PIPELINE AT MADURA STRAIT) - SINGGIH NUGROHO (NIM : 13105045); Pembimbing : Prof. Dr. Ir. IGN Wiratmaja Puja, BANAR
Submarine pipeline system is the transmission of the oil and natural gas from offshore facility to onshore facility. Submarine pipeline damage or failure could generate the serious impacts and big losses. Therefore, submarine pipeline design must be analyzed comprehensively and must be evaluated based on criteria contained in code and standard for ensuring that submarine pipeline system is safe to be operated. This final project conducted the stress analysis for in-plane, hydrotest and operation condition based on criteria contained in the DNV OS F101 (Submarine pipeline System). As a case study, the author analyzed the stress of submarine pipeline at Madura strait. This submarine pipeline transmitted natural gas from offshore facility at Madura strait to the next processing facility at Grati, East Java. The aim of stress analysis which has been done by the author is to evaluate the ratio between stress in pipeline with allowable stress. The result of the analysis showed that the maximum ratio at submarine pipeline equal to 161% in pipe bend area at operation condition. So, this condition indicated that submarine pipeline was failed. Therefore the author suggested to make some modifications of submarine pipeline by changing the pipeline route and using schedule 80 (pipe wall thickness 0,75 in), so the result of these modification were obtained that the submarine pipeline is safe to be operated with the maximum pressure ratio 79,6%.